Regulatory Dendritic Cells for Immunotherapy in Immunologic Diseases - Gordon, John R.; Ma, Yanna; Churchman, Laura; Gordon, Sara A.; Dawicki, Wojciech (Frontiers in Immunology, 2014)
We recognize well the abilities of dendritic cells to activate effector T cell responses to an array of antigens and we think of these cells in this context as pre-eminent antigen presenting cells, but dendritic cells are also critical to the induction of immunologic tolerance. Herein we review our knowledge around the different kinds of tolerogenic or regulatory dendritic cells that are present or can be induced in experimental settings and humans, how they operate and the disease in which they are effective, from allergic to autoimmune diseases and transplant tolerance. Central messages that arise from these cumulative studies clearly indicate that the agent(s) used to induce the tolerogenic phenotype and the status of the dendritic cell at the time of induction influence not only the phenotype of the dendritic cell, but also that of the regulatory T cell responses that they in turn mobilize. For example, while many, if not most, types of induced regulatory dendritic cells lead CD4+ naïve or effector T cells to adopt a CD25+Foxp3+ Treg phenotype, exposure of Langerhan’s cells or dermal dendritic cells to vitamin D leads in one case to the downstream induction of CD25+Foxp3+ regulatory T cell responses, while in the other to Foxp3- type 1 regulatory T cells (Tr1) responses. Similarly, exposure of human immature versus semi-mature dendritic cells to IL-10 leads to distinct regulatory T cell outcomes. Thus, it should be possible to shape our dendritic cell immunotherapy approaches for selective induction of different types of T cell tolerance or to simultaneously induce multiple types of regulatory T cell responses. This may prove an important option as we target diseases in different anatomic compartments or with divergent pathologies in the clinic. Finally, we provide an overview of the use and potential use of these cells clinically, highlighting their potential as tools in an array of settings.